Association between diet and gallstones of cholesterol and pigment among patients with cholecystectomy: a case-control study in Korea. Issue 1 (December 2017) - Park, Yongsoon; Kim, Doyeon; Lee, Ju; Kim, Yu; Jeong, Yoon; Lee, Kyeong; Choi, Dongho
Abstract Background The prevalence of cholesterol gallstones is high in Western populations, while pigment gallstones are common in Asian populations. Dietary factors are suggested to be associated with gallstone risk, but their relationship with gallstone type has not been evaluated. This study investigated the association between diet and risk of cholesterol gallstone or pigment gallstone in a Korean population whose dietary pattern and type of gallstone were changed during the last 30 years. Methods Patients with cholesterol (n  = 40) and pigment (n  = 59) gallstones were recruited after laparoscopic cholecystectomy and were compared with those of age- and sex-matched controls without gallstones (n  = 99). Dietary intakes were assessed by trained dietitians using a semi-quantitative food frequency questionnaire. Multinomial logistic regression analysis was performed to calculate odds ratios and 95% confidence intervals to examine the associations between diet and risk for type of gallstones adjusted by potential confounders. Results Patients with cholesterol gallstone consumed more lipid, animal lipid, beef, pork, and fried food than those with pigment gallstones and control, while patients with pigment gallstone consumed more carbohydrate and noodles than patients with cholesterol gallstone and control. In multinomial logistic regression analysis using control as reference group, dietary pattern with high consumption of beef, pork, and fried food was associated with risk of cholesterol gallstones, while there was no association between the risk of pigment gallstone and dietary pattern. In addition, control consumed more alcohol than patients with cholesterol and pigment gallstones. Conclusions The present study suggested consumption of fat from meat and fried foods increased the risk of cholesterol gallstone, and intake of carbohydrate from noodles increased the risk of pigment gallstone.